CD52-Negative NK cells are abundant in the liver and less susceptible to alemtuzumab treatment - Hotta, R; Ohira, M; Matsuura, T; Muraoka, I; Tryphonopoulos, P; Fan, J; Tekin, A; Selvaggi, G; Levi, D; Ruiz, P; Ricordi, C; Vianna, R; et al. (Public Library of Science, 2016)
Background T-cell depleting strategies have become an integral part of immunosuppressive regimens in organ transplantation. Alemtuzumab is a humanized monoclonal antibody against CD52, a cell-surface antigen on several immune cells. It has been suggested that lymphocyte depletion increases the risk of serious infections. However, this has not been observed with short-term alemtuzumab treatment in an organ transplant setting. For induction therapy using alemtuzumab following liver transplantation, we found that T- and B-cell numbers declined rapidly after alemtuzumab therapy; however, the natural killer (NK) cell number was sustained. NK cells are important effectors of innate immunity. Since the effects of alemtuzumab on NK cell functions, especially those of liver NK cells, are unknown, this study aimed to investigate this in detail. Methods To assess the effect of alemtuzumab on NK cells, samples were obtained from 7 organ donors and examined by flow cytometry using Annexin V and propidium iodide. Phenotypical and functional differences within subsets of NK cells with different levels of CD52 expression were determined by flow cytometry and in vitro cytotoxicity assays. Results CD52 expression on NK cells was lower than that on other lymphocyte subsets. The liver contained a large number of CD52− NK cells compared with the peripheral blood. In vitro treatment of liver-derived NK cells with alemtuzumab did not result in cell death. In contrast, co-incubation with alemtuzumab induced cell death in peripheral blood mononuclear cells and non-NK cells in the liver. Furthermore, CD52− liver NK cells were more cytotoxic and produced more IFN-γ than CD52+ NK cells after cytokine activation. Conclusion The liver contains a large number of CD52− NK cells. These cells are refractory to alemtuzumab and have robust activity. These findings indicate that CD52− NK cells persist and could protect against infection after alemtuzumab-based lymphocyte depletion.